Critical assessment of the nortecubana fault - Cotilla Rodríguez, Mario Ovtavio; Álvarez Gómez, José Leonardo (Nexo Revista Científica, 2023)
The Nortecubana fault is an extensive geological structure (~1.200 km), arched (concave to the south), segmented (into 4 parts) and submarine, in the contemporary plane, seismically active, to the north of Cuba, and which constitutes the northern limit of the megablock. 1) SW-NE -Consolación del Norte, Guane and Pinar faults-; 2) NW-SE -Cubitas, Las Villas and Tuinicú faults-. Historical earthquakes and those of the instrumental period (Mmax 6.2) are associated with it; all interior plate type (North American). The regional category is level 5. Anthropic activity has generated some earthquakes, all of low energy. There are no fatalities associated with fault activity, and it has only generated 2 local tsunamis. It is argued against the incorrect relationship that other authors have assumed with the Northern (North of Hispaniola) and Oriente (South of Eastern Cuba) faults.